Zn1-xGaxO1-yNy – Graphene oxide nanocomposite for enhanced visible – Light photocatalytic activity. (June 2019) - Janani, R.; Menon, Sumithra Sivadas; Bhalerao, Gopalkrishna; Gupta, Bhavana; Singh, Shubra
Abstract: Zn1-x Gax O1-y Ny oxynitride has gained immense importance in the field of photocatalytic hydrogen generation and organic dye degradation; especially due to its narrow band gap, making it active under visible spectra. In the present work, the activity of Zn1-x Gax O1-y Ny oxynitride photocatalyst has been enhanced significantly when a composite of graphene oxide with Zn1-x Gax O1-y Ny is designed. Graphene oxide is synthesized via oxidative treatment of graphite by modified Hummers method while Zn1-x Gax O1-y Ny sample is synthesized via solution combustion technique. The integration of graphene oxide with the solid solution was carried out via two different techniques namely solution combustion and sonication route. The ability of the compound to generate charge carriers and produce photocurrent was explored using Photoelectrochemical measurements. Photocatalytic activity was evaluated by the degradation of organic dye under sunlight. Highlights: Two different simple methods for synthesis of nanocomposites between Zn1-x Gax O1-y Ny and Graphene Oxide. Photocatalytic dye degradation under natural sunlight and Photoelectrochemical measurements under visible light radiation. Integration with Graphene oxide results in better photocatalytic activity.